Impulsive Buying pada Pengguna Shopee Generasi Z: Gaya Hidup, Fitur Spaylater dan Word of Mouth - Akib, Nasifa Tridasari; Yuliana, Ika; Anggriani, Rini; Jati, Lanang Jatmiko (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Online shopping is now an important part of the lifestyle of Generation Z due to the rapid development of e-commerce applications. Generation Z in the city of Mataram tends to have a lifestyle that follows things that are on the rise or commonly referred to as ‘fomo’. In order to fulfill personal desires in following a trend in the context of the lifestyle of Generation Z tend to do shopping without thinking. Generation Z, which is called the digital generation because it is close to technology, is the future consumer of e-commerce platforms. The purpose of this study was to determine the effect of lifestyle, Spaylater features and word of mouth on impulsive buying on Shopee Generation Z users. This study uses quantitative methods with descriptive and causality approaches. Respondents in this study amounted to 100 dihited with lemeshow formula, and data processing tools using SPSS 22. The results of this study that lifestyle has a positive and partially significant effect on impulsive buying. The Spaylater feature has a positive and partially insignificant effect on impulsive buying. Word of mouth has a positive and significant effect on impulsive buying. Lifestyle, Spaylater feature and Word of Mouth have a positive and significant effect simultaneously on Impulsive buying.